Fonotaktik Bahasa Jawa Kuno - Muhammad Musleh Febri Ardiansyah; Atin Fitriana (PRASASTI: Journal of Linguistics, 2024)
The phonotactics of Old Javanese has been described by Ogloblin (1991), Mardiwarsito and Kridalaksana (2012), and Suarka (2018). In general, these studies explain the phonotactics of Old Javanese based on the number of phonotactic patterns found along with examples of words that represent each of these tribal patterns. However, the three studies have not explained the specific types of phonemes that are distributed in the tribal patterns in Old Javanese. The purpose of this research is to describe the distribution of Old Javanese phonemes in monosyllabic words. This research uses a qualitative method. The data sources used are the Old Javanese-Indonesian dictionary (Zoetmulder, 2006) and the online dictionary of the Old Javanese language http://sealang.net/ojed/. This research uses the classification of Old Javanese tribal patterns by Suarka (2018); there are 11 phonotactic patterns in Old Javanese. Data collection was done by searching and recording words containing the 11 Old Javanese tribal patterns in the Old Javanese-Indonesian dictionary (Zoetmulder, 2006). The data were grouped based on the type of phonemes that occupy the existing tribal patterns. This research produces a type of phoneme that tends to be distributed to occupy the position of the tribal pattern in monosyllabic words.